1987
DOI: 10.1115/1.3269394
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Modal Coupling on the Acoustic Power Radiation From Panels

Abstract: The effects of modal coupling on the acoustic power radiated from line forced panels of unit width with s-s (simply supported-simply supported) and c-c (clamped-clamped) end conditions have been studied. The expressions for the power radiated by the total square terms and by the coupling terms in these two one-dimensional problems were derived using Heckl’s power integral. A qualitative and quantitative discussion regarding the properties of Pmn (the power radiation coefficient of the m- and nth modes) and Dmn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Therefore, an accurate characterization of the sound-structural interaction is essential for the prediction of acoustic field. Since conventional modal-based methods heavily rely on the availability of the acoustic modes, which are not analytically known in the presence of geometry irregularity, most of previous investigations focused on systems with perfect geometry and homogeneous structural properties [7][8][9][10]. In practice, imperfections (geometrical distortion or structural parameter uncertainty) always exist to a certain extent, which may lead to significant discrepancy from results obtained using idealized models, in terms of both eigen-frequencies and responses of the system.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, an accurate characterization of the sound-structural interaction is essential for the prediction of acoustic field. Since conventional modal-based methods heavily rely on the availability of the acoustic modes, which are not analytically known in the presence of geometry irregularity, most of previous investigations focused on systems with perfect geometry and homogeneous structural properties [7][8][9][10]. In practice, imperfections (geometrical distortion or structural parameter uncertainty) always exist to a certain extent, which may lead to significant discrepancy from results obtained using idealized models, in terms of both eigen-frequencies and responses of the system.…”
Section: Introductionmentioning
confidence: 97%
“…Early researches in this field were presented by Junger and Feit [1] and Dowell et al [2,3], who developed a comprehensive modal-based theoretical framework for interior sound field prediction. Since then, a large amount of efforts has been devoted to investigating the vibro-acoustic behavior of such systems, such as analysis of structural-acoustic modal interaction [4][5][6][7] and sound radiation prediction [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the cross-modal coupling on the radiation from a panel was pointed out by Keltie and Peng in [11]; it was noted that, particularly at low frequencies and under off-resonant excitation, this contribution should not be neglected. [12] demonstrated that the cross-modal contributions are only non-zero for pairs of modes that are either both odd or both even in a given direction.…”
Section: Introductionmentioning
confidence: 99%
“…Although the potential problem of only considering the self-powers generated independently by each mode has long been recognized [14], there are few publications in the literature about the characteristics of the mutual-radiation resistances and their impact to the radiated sound power. Keltie and Peng [15] investigated the e!ects of the cross-modal coupling on acoustic radiation from one-dimensional (1-D) panels by varying force locations. It was demonstrated that the contributions due to the cross-terms could be important in a low-frequency range or for a non-resonant response.…”
Section: Introductionmentioning
confidence: 99%